The Journal of Family Practice 2021
DOI: 10.12788/jfp.0308
|View full text |Cite
|
Sign up to set email alerts
|

Which injections are effective for lateral epicondylitis?

Abstract: A Q Which injections are effective for lateral epicondylitis? placebo injections actually improve lateral epicondylitis at high rates. No other injections convincingly improve it better than placebo.Corticosteroid injection is not superior to saline or anesthetic injection (strength of recommendation [SOR] A, systematic review of randomized controlled trials [RCTs]). Platelet-rich plasma (PRP) injection is not superior to saline injection (SOR A, meta-analysis of RCTs).Botulinum toxin injection, compared to sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…While there is a lack of studies focusing on neural therapy for LE treatment, several studies have evaluated other types of injections [11][12][13][14][15]. These injection treatments are also recommended for patients who do not respond to alternative methods.…”
Section: Discussionmentioning
confidence: 99%
“…While there is a lack of studies focusing on neural therapy for LE treatment, several studies have evaluated other types of injections [11][12][13][14][15]. These injection treatments are also recommended for patients who do not respond to alternative methods.…”
Section: Discussionmentioning
confidence: 99%
“…Tonks et al thought that steroid injection therapy was the best conservative treatment and that the symptoms of pain could be rapidly relieved during the initial phases of the condition [10]. Some experts suggested that corticosteroid injection should not be used to treat most patients with tennis elbow who exhibit a symptom duration of less than 12 months and that this approach might be less beneficial to the long-term outcomes of the patient [11]. In the long term, physiotherapy became the best option, followed by a wait-and-see policy, but the recovery period was still long [12].…”
Section: Introductionmentioning
confidence: 99%
“…Tonks et al thought that steroid injection therapy was the best conservative treatment and that the symptoms of pain could be rapidly relieved during the initial phases of the condition [10]. Some experts suggested that corticosteroid injection should not be used to treat most patients with tennis elbow who exhibit a symptom duration of less than 12 months and that this approach might be less bene cial to the long-term outcomes of the patient [11]. In the long term, physiotherapy became the best option, followed by a wait-and-see policy, but the recovery period was still long.…”
Section: Introductionmentioning
confidence: 99%